The Effect Of Family Functioning On Moral Disengagement In Adolescents Mediated By Religiosity - Eri Yudhani; Fuad Nashori; Muhamad Uyun (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2020)
This study aimed to observe the correlation of family functionality and moral disengagement among the adolescents mediated by religiosity. It involved the adolescents (N =263) aged from 13 to 17 years old. The measurement tools used in this study included the scale of family functionality using family assessment device (FAD) made by Epstein et al. (1983), The scale of Indonesian-Psychological Measurement of Islamic Religiousness (I-PMIR) arranged by Salsabila et al. (2019), and Mechanisms of Moral Disengagement developed by Bandura et al. (1996). Correlation coefficient showed that the family functionality was correlated with religiosity and moral disengagement. In contrast, religiosity was negatively correlated with moral disengagement. Analysis used Structural Equation Modelling (SEM) program AMOS 24, The results of this study showed that the religiosity fully mediated the correlation of family functionality and moral disengagement. The implementation of this study showed that to decrease the level of moral disengagement among adolescents there should be the involvement of communication among the family members and parents need to embed the religious values in family and make the adolescents to habitually do the order that has been suggested by religion.